2012
DOI: 10.24071/llt.2012.150101
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Problems in Writing Paraphrases in Research Paper Writing Class

Abstract: Paraphrase is one of the techniques of incorporating sources in which every writer is allowed to borrow the author's ideas and restate them into their own words. Based on the previous study, it was found that English Language Education Study Program (ELESP) students, Sanata Dharma University, were unable to paraphrase properly since they tended to copy the author's words directly. If this problem was continuously ignored, it would be dangerous for the students because they could be charged with inadvertent pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Many researchers concern about plagiarism where in many context of witing classess, the majority of students use copying as a major strategy in their writing text (Fazilatfar et al, 2018). Many students also in another context of study, found that the biggest problem faced by teachers when teaching writing is that the majority of students do word-for-word plagiarism (Hayuningrum, 2021). Thus, lecturers also work hard on how to make their students to not committing to plagiarism (Choi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers concern about plagiarism where in many context of witing classess, the majority of students use copying as a major strategy in their writing text (Fazilatfar et al, 2018). Many students also in another context of study, found that the biggest problem faced by teachers when teaching writing is that the majority of students do word-for-word plagiarism (Hayuningrum, 2021). Thus, lecturers also work hard on how to make their students to not committing to plagiarism (Choi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Paraphrasing is a technique of incorporating sources by borrowing the author's ideas but they are restated in the writer's own language. The study by Hayuningrum on students' problems of writing paraphrases for academic writing found forgetting to documents, including too much of the original, misreading the original, leaving important information, adding opinion, expanding or narrowing the meaning, and substituting inappropriate synonyms as common problems in paraphrasing [36]. Though those research findings were of students, they may serve as warnings for lecturers in writing phrases.…”
Section: Discussionmentioning
confidence: 97%
“…Paraphrasing is a valuable and needed skill in academic writing. However, these skills are not easily mastered by students (Hayuningrum & Yulia, 2012). When paraphrasing, for example, a journal article, one's vocabulary, strength, and understanding will be tested.…”
Section: Introductionmentioning
confidence: 99%